STABILITY COMPARISON OF TULASI (Ocimum tenuiflorum L.) LEAF GEL HAND SANITIZER USING 0.5% AND 1% CMC-Na - Swari, Dewa Ayu Made Adnya; Udayana A, Ni Putu; Shantini S, Ni Made Dharma (Journal Pharmaceutical Science and Application; Vol 2 No 1 (2020): Journal Pharmaceutical Science and ApplicationDO - 10.24843/JPSA.2020.v02.i01.p04, 2020)
Background: Hand sanitizers contain 62% alcohol, softener and moisturizer. High alcohol content is able to irritate and make hands dry. A suitable moisturizer is needed for this preparation. Objective: The aim of this study is to evaluate the physical quality of gel hand sanitizer formulation of Ocimum tenuiflorum with CMC-Na as a gelling agent at a concentration of 0.5% and 1% CMC-Na. Methods: Data were collected at week-0,1,2,3,4, and replication is performed three times at each concentration of each measurement. The test results of the spread and adhesion data analysis using SPSS with a 95% confidence level. Results: Dispersive power and adhesion showed no significant difference (p <0.05) at week 0 and week 4 means second-hand sanitizer gel formulation concentration is not stable. Gel hand sanitizer leaves of Tulasi ( Ocimum tenuiflorum ) at a concentration of 1% CMC-Na stable from week 0 to week 3, while the concentration of 0.5% CMC-Na change at week 2. Gel hand sanitizer leaves of Tulasi ( Ocimum tenuiflorum ) with a gelling agent CMC-Na should need to be titrated. Conclusion: Gel hand sanitizer leaves of Tulasi ( Ocimum tenuiflorum ) that use concentrations of 1% CMC-Na as a gelling agent have a physical quality that is more stable than the organoleptic test concentration of 0.5% CMC-Na. Keywords: Hand sanitizer, Ocimum tenuiflorum L., CMC-Na, Physical quality evaluation